Cellular and genetic damage as determinants of pesticide toxicity - Valbuena, Duvan Sebastián; Meléndez-Flórez, María Paula; Villegas, Victoria Eugenia; Sánchez, Magda Carolina; Rondón-Lagos, Milena (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The use of pesticides in Colombia has allowed effective pest control, increasing agricultural, forestry and livestock productivity. However, both occupational and environmental exposure to pesticides can generate harmful effects on human health, since they can induce damage to genetic material, causing the development of diseases, including cancer. Although the harmful effects caused by exposure to pesticides are widely known, specific information about genomic damage (gene and chromosomal damage) generated by exposure to them is scarce or absent. This review aims to describe the cellular and genetic effects induced by exposure to pesticides, as well as their implications for disease development. Considering the wide use of pesticides in the world, as well as their impacts on health, increasing our knowledge of their harmful effects will allow us to establish future possibilities for applying tests for the early detection of diseases, as well as developing programs and/or preventive actions aimed at protecting the most vulnerable individuals in occupational and environmental settings.